Blended Amish blessings [large type] - Johns, Patricia (Romance writer) (Redemption's Amish legacies, 2021)
"The last thing widower Paul Ebersole needs after discovering he has a teenage daughter and a granddaughter is for his kitten to cause havoc in Haddie Petersheim's Amish creamery. Yet working with Haddie to repair her store might be the answer to his prayers ... if he and the widowed mother join forces on their parenting problems. But what happens when their two little families start to feel like one?" -- Page 4 of cover.